2014
DOI: 10.1103/physrevc.90.064309
|View full text |Cite
|
Sign up to set email alerts
|

Shape coexistence and triaxiality in nuclei nearZr80

Abstract: Total-Routhian-Surface calculations have been performed to investigate the shape evolutions of A ∼ 80 nuclei, 80−84 Zr, 76−80 Sr and 84,86 Mo. Shape coexistences of spherical, prolate and oblate deformations have been found in these nuclei. Particularly for the nuclei, 80 Sr and 82 Zr, the energy differences between two shape-coexisting states are less than 220 keV. At high spins, the g 9/2 shell plays an important role for shape evolutions. It has been found that the alignment of the g 9/2 quasi-particles dri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…IIIC in Ref. [15]) has been shown to be very successfully in both nuclear spectroscopy [68][69][70][71] and binding energy [15] calculations. In particular, it gives a good description of the nuclear momentum of inertia and high spin states.…”
Section: Global Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…IIIC in Ref. [15]) has been shown to be very successfully in both nuclear spectroscopy [68][69][70][71] and binding energy [15] calculations. In particular, it gives a good description of the nuclear momentum of inertia and high spin states.…”
Section: Global Calculationsmentioning
confidence: 99%
“…There is a long history in nuclear physics studying the so-called shape coexistence and many prominent examples have been found [68,75,76]. It is also important for our study of radioactive alpha [77] and proton decays [65].…”
Section: Iii4 the Second Minimummentioning
confidence: 99%
“…However, it is definitely not responsible for the EI closures which demand splittings much larger that the l • s one provided by the NN interactions. To fix ideas: in 48 Ca they would produce a f 7/2 − p 3/2 single particle gap equal to that in 41 Ca i.e., 2.5 MeV smaller than the observed one. A discrepancy that increases to some 4.5 MeV in 56 Ni.…”
Section: The Natural Zbm (Or Eei) Model Spacesmentioning
confidence: 99%
“…The main discrepancy with their work is in the positioning of the closed shell, which in the potential energy surface [58, Fig.2] comes some 4 MeV below the deformed minima which we attribute to underbinding of the latter due to the monopole effect described above. Other calculations for 80 Zr include [26,27,48].…”
Section: B Monopole Vs Single Particle Fieldmentioning
confidence: 99%
“…For example, the N = Z = 40 nucleus 80 Zr is one of the most deformed nuclei known so far with a quadrupole deformation of β 2 ≈ 0.4 [5]. Total-Routhian-surface calculations have indicated that the * markus.k.vilen@student.jyu.fi g 9/2 shell plays an important role in the shape evolution, with spherical, prolate, oblate, and triaxial shapes predicted [6]. Even possible tetrahedral deformation has been proposed to exist in the region [7].…”
Section: Introductionmentioning
confidence: 99%